2019
DOI: 10.1002/ecy.2879
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐trophic interactions mediate the spread of a vector‐borne plant pathogen

Abstract: Many insect herbivores are vectors that transmit plant pathogens as they forage. Within food webs, vectors interact with a range of host plants, other herbivores, and predators. Yet, few studies have examined how tri‐trophic interactions involving vectors affect the spread of pathogens. Here we assessed effects of food web structure on aphid vectors and the prevalence of an aphid‐borne persistent pathogen (Pea enation mosaic virus, PEMV) in pea plants. We experimentally manipulated ladybird predators, alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Such trade‐offs affect both natural enemies and the pests and pathogens which they help to control (Karp et al., 2018; Plantegenest et al., 2007). Effects of natural enemies can also be counter‐intuitive, for example by promoting increased movement of pathogen vectors (Clark, Basu, Lee, & Crowder, 2019; Crowder et al., 2019). The complexity of these interrelationships means that positive effects of semi‐natural habitat on natural enemy abundance and richness do not always translate to improved pest regulation or enhanced yields (Karp et al., 2018; Martin et al., 2013, 2019; Mitchell, Bennett, & Gonzalez, 2014; Smith et al., 2020; Tscharntke et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Such trade‐offs affect both natural enemies and the pests and pathogens which they help to control (Karp et al., 2018; Plantegenest et al., 2007). Effects of natural enemies can also be counter‐intuitive, for example by promoting increased movement of pathogen vectors (Clark, Basu, Lee, & Crowder, 2019; Crowder et al., 2019). The complexity of these interrelationships means that positive effects of semi‐natural habitat on natural enemy abundance and richness do not always translate to improved pest regulation or enhanced yields (Karp et al., 2018; Martin et al., 2013, 2019; Mitchell, Bennett, & Gonzalez, 2014; Smith et al., 2020; Tscharntke et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Most plant viruses rely on a third party for host-host spread, with sap-sucking insects from the order Hemiptera (aphids, whiteflies, planthoppers, and leafhoppers) being by far the most widespread vectors [1,2]. Thus, virus transmission during the feeding process relies on a complex set of interactions that are the result of the co-evolution of at least three partners: the pathogen, the vector, and the host plant-each with its own behaviour, population, and community dynamics [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Box 5 Enemy-risk effects and biological control of vectors of plant disease One of the most damaging ways that insect herbivores affect their host plants is by acting as vectors of plant pathogens. Biological control agents can clearly slow the spread of vectored pathogens by suppressing vector population densities; as both consumptive and non-consumptive effects can depress population growth rates of insect vector populations, both can contribute to this ecosystem service (Landis and Van der Werf, 1997;Moore et al, 2009;Finke, 2012;Long and Finke, 2015;Clark et al, 2019).…”
Section: Effects Of Multiple Enemies On Pestsmentioning
confidence: 99%
“…Thus, the net effect of biological control on disease prevalence can be negative, neutral or positive, depending on the relative magnitudes of consumptive effects and enemy-risk effects and the details of the interactions (Finke, 2012;Crowder et al, 2019). The empirical record has shown that outcomes can depend on the identity of the biocontrol agents, the herbivore and the pathogen (Nelson and Rosenheim, 2006;Belliure et al, 2011;Dumont et al, 2015;Clark et al, 2019); in particular, predator-prey interactions that result in strong prey dispersal in response to predation risk or actual predator attacks often result in short-term increases in disease transmission any time pathogen acquisition and transmission by the vector is not interrupted by the decision to leave a feeding site.…”
Section: Effects Of Multiple Enemies On Pestsmentioning
confidence: 99%